العلاقة بين السمات الشخصية والميول المهنية لدى عينة من طلبة التعليم الثانوي - عز, إيمان (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث الحالي إلى تعرّف طبيعة العلاقة بين السمات الشخصية والميول المهنية لدى عينة من طلبة التعليم الثانوي الحكومي في مدينة طرطوس، وكذلك الفروق في كل من السمات الشخصية، والميول المهنية بين الطلبة الذكور والإناث، وبلغت العينة /104/ طالباً وطالبة، إذ استخدم أداتي بحث هما مقياس "سترونغ" Strong للميول المهنية ويتضمن ستة مجالات أساسية من الميول هي( الواقعي، البحثي، الفني، الاجتماعي، المغامرة، التقليدي)، واختبار "جاكسون" Jackson المعدل للشخصية وهو مؤلف من /300/ بند يقيس خمس عشرة سمة، تمّ التوصل إلى النتائج الآتية: 1- يوجد ارتباط موجب بين الميل الواقعي وسمات الشخصية،(التحمل، والإبداع، واتساع الاهتمام، والمخاطرة)، والميل البحثي وسمات،(التحمل، والإبداع، واتساع الاهتمام، والتنظيم)، والميل الاجتماعي وسمات (القلق، والتعاطف)، والميل للمغامرة وسمات، ( اتساع الاهتمام، والمخاطرة)، والميل التقليدي، وسمات(اتساع الاهتمام، والمخاطرة) . 2- يوجد ارتباط سلبي بين الميل الواقعي وسمات الشخصية، (التعقيد، والتنظيم)، والميل الفني وسمة(المسؤولية)، والميل للمغامرة وسمات،(القيم التقليدية، والتنظيم)، والميل التقليدي وسمات،(قيم تقليدية، والتنظيم). 3- يوجد فروق ذات دلالة إحصائية في سمات الشخصية،(العامل التحليلي، والاعتمادية) لصالح الإناث. 4- يوجد فروق ذات دلالة إحصائية في الميول المهنية،(الواقعي، والتقليدي) لصالح الذكور. The aim of this study is to define the nature of the correlated relation between the personality traits and the vocational interests of the governal secondary education students in Tartous and to define the difference between male and female students according them. The sample is(104) students, and Strong Interest Inventory(SII), Jackson personality Inventory- Revised instruments. This study leads to the following: -There is a positive correlation between Realistic interest and personality traits such as(tolerance, innovation, breadth of interest, risk taking), the Research interest such as (tolerance, innovation, breadth of interest, and organization), the Social interest(anxiety, and empathy), the Opportunistic (breadth of interest, and risk taking), and between Traditional interest (breadth of interest, and risk taking). - There is negative correlation between Realistic interest and personality traits such(complexity, and organization), artistic interest ( responsibility),Opportunistic(traditional values, and organization)and between Traditional interest(traditional values, and organization). -There are statistical difference in the traits of personality as Analytical Factor and dependable in favor Females. - There are satirical difference in the vocational interests such as Realistic and Traditional in favor males.